Self-representation questionnaire for youths in residential care - Patrício, J. N. (2016)
The objective of this study was to develop and test an instrument to measure self-representation of youths in residential care. The sample was composed of 848 youths in residential care that filled the Self-representation Questionnaire for Youth in Residential Care (SRQYRC). The Child Behavior Checklist was applied for each youth to test the SRQYRC construct validity. Descriptive analyses, correlations and exploratory and confirmatory factor analyses were conducted to analyze the psychometric properties of this instrument. The results indicated that SRQYRC is organized in 6 dimensions (Social, Competence, Relational, Behavioral, Emotional, and Misfit) and 2 second order factors (Global negative representation and Global positive representation). The instrument presents good initial psychometric properties, namely it has adequate reliability and construct validity (i.e., self-representation showed the expected relation with mental health outcomes). We found the following trends: 1) that female youths described themselves as less competent and had a more global negative self-representation than male youths; and 2) older participants described themselves as more competent but also having more emotional problems than younger participants. We concluded that the SRQYRC is a valid and reliable instrument to measure youth self-representation in care. Furthermore it can be used to identify which youths need intervention to develop a more positive self-representation.